Study on sustained-release metformin hydrochloride from matrix tablet: Influence of hydrophilic polymers and in vitro evaluation - Wadher, Kamlesh J; Kakde, Rajendra B; Umekar, Milind J (International Journal of Pharmaceutical Investigation)
The overall objective of the present work was to develop an oral sustained-release (SR) metformin tablet prepared by the direct compression method, using hydrophilic hydroxylpropylmethylcellulose (HPMC) and Guar gum polymer alone and in combination at different concentrations. Metformin hydrochloride (HCl), a biguanide, has a relatively short plasma half-life and low absolute bioavailability. All the batches were evaluated for thickness, weight variation, hardness and drug content uniformity and in vitro drug release. Mean dissolution time is used to characterize the drug release rate from a dosage form, and indicates the drug release-retarding efficiency of the polymer. The hydrophilic matrix of HPMC alone could not control the Metformin release effectively for 12 h whereas when combined with Guar gum, it could slow down the release of drug and, thus, can be successfully employed for formulating SR matrix tablets. Fitting the data to the Korsmeyer equation indicated that diffusion along with erosion could be the mechanism of drug release. Similarity factor ƒ2 values suggest that the test and reference profiles are identical.
Keywords: Guar gum; hydroxylpropylmethylcellulose K100M; matrix tablets; release kinetics; similarity factors